Is it true that environment, social & governance can make a company indefficient, (case study on the sri-kehati index) - Alhazami, Lutfi; Mareta, Sigit; Doktoralina, Caturida; Lestari, Lestari (Jurnal Mantik, 2024)
This research aims to investigate the influence of ESG scores on firm performance. Furthermore, this study measures firm performance by assessing total asset turnover. The data collected consist of historical annual data spanning 5 years from companies listed in the Sri-Kehati index. This research employs regression analysis. It adopts a quantitative approach, where secondary data between 2019-2023 are obtained from databases such as Refinitiv Eikon, RTI Business, Sustainalytics, & MSCI ESG Ratings. The study finds that the relationship between ESG scores and total asset turnover is negative, indicating that an increase in ESG scores leads to less efficient asset utilization.